2015
DOI: 10.7150/ijms.11078
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Response to Mechanical Unloading in Bone Loss, Microarchitecture, and Bone Turnover Markers

Abstract: Background: Sclerostin, encoded by the SOST gene, has been implicated in the response to mechanical loading in bone. Some studies demonstrated that unloading leads to up-regulated SOST expression, which may induce bone loss.Purpose: Most reported studies regarding the changes caused by mechanical unloading were only based on a single site. Considering that the longitudinal bone growth leads to cells of different age with different sensitivity to unloading, we hypothesized that bone turnover in response to unlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Sclerostin (SOST) is a protein produced by bone cells and plays an important regulatory role in bone metabolism [ 16 ]. Under normal conditions, Sclerostin regulates bone metabolism by inhibiting the process of bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sclerostin (SOST) is a protein produced by bone cells and plays an important regulatory role in bone metabolism [ 16 ]. Under normal conditions, Sclerostin regulates bone metabolism by inhibiting the process of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, logistic regression analysis was used to analyze the factors influencing the occurrence of AAC in PD patients, and the results also suggested a significant role of SOST (OR = 1.006, 95% CI: 1.000-1.011, P = 0.038) in the development of AAC in PD patients. Sclerostin (SOST) is a protein produced by bone cells and plays an important regulatory role in bone metabolism [16]. Under normal conditions, Sclerostin regulates bone metabolism by inhibiting the process of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Since several risk factors have been associated with osteoporosis like age [ 22 ], menopausal status [ 23 ], hormonal dysregulation [ 24 ], malabsorption [ 25 ], side effects to medication like prednisolone [ 26 ], smoking [ 27 ], low BMI [ 28 ], immobilization [ 29 ], and disuse [ 30 ], it is crucial to select the appropriate animal model. Previous studies have revealed that the magnitude of bone loss varies between the different models used [ 7 , 11 , 31 ]. In addition, it has also been established that the bone loss observed by a particular disuse model is strain-specific underlining the importance of the genetic background of the animals used [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%